Between sonata form and borrowing technique: the overtures of Stanisław Moniuszko - Keym, Stefan (Chopin Review, 2025)
The genre of the overture, which stands on the border between symphonic music and opera, has often been underestimated, even though it possessed great innovative potential for this very reason. The present article demonstrates this using the overtures of Polish composer Stanisław Moniuszko. The focus is on the relationship between the sonata form used in at least five of his overtures and the potpourri technique, in which melodies and other material from the subsequent opera are used in the overture. Both the formal structure and the semantic level are examined. Moniuszko followed typical genre trends of his time, but also found original solutions of his own. His overtures indicate a growing interest in transitions and in a more careful integration of material from the respective opera. Furthermore, the semantic connotations of the combination of this material become more complex in the later works.